Trends in abundance and wintering phenology of the Dark-bellied Brent Goose Branta b. bernicla in France between 1982 and 2012 - Valéry, Loïc; Schricke, Vincent (Wildfowl, 2013)
Trends in abundance, the timing of arrival and departure, and the number of goose-days at internationally important sites, are presented for Dark-bellied Brent Geese Branta bernicla bernicla wintering in France during 1982–2012 inclusive. Numbers wintering in France increased more rapidly than the increase in the population as a whole: c. 30% of the world population occurred in France in 1982 and just over half in 2012. Throughout the past 30 years, c. 75% of Brent Geese wintering in France have concentrated at just six sites. Two of them (Bassin d’Arcachon and Golfe du Morbihan) have shown a sharp rise in numbers in mid-January, most notably a fivefold increase in 30 years at the Bassin d’Arcachon, which now accounts for c. 43% of the total in France (compared with c. 21% in 1982) and c. 22% of the world population (c. 5% in 1982). Wintering phenology at the six main sites, determined from the dates on which 50% of the annual peak count had arrived and departed, has varied over time. At five of the sites, this proportion of Brent Geese now arrives 3–4 weeks earlier than 30 years ago. The total number of goose-days has increased almost fivefold at Bassin d’Arcachon and doubled in Baie de Bourgneuf, although the reasons for these changes remain unclear. In particular, the increase at Bassin d’Arcachon merits investigation, given a long-term decline in eelgrass Zostera sp. abundance at this site.